Simulation of Nanofluid Flow in a Micro-Heat Sink With Corrugated Walls Considering the Effect of Nanoparticle Diameter on Heat Sink Efficiency - Khetib, Yacine; Abo-Dief, Hala M.; Alanazi, Abdullah K.; Cheraghian, Goshtasp; Sajadi, S. Mohammad; Sharifpur, Mohsen (Frontiers in Energy Research, 2021)
In this numerical work, the cooling performance of water–Al2O3 nanofluid (NF) in a novel microchannel heat sink with wavy walls (WMH-S) is investigated. The focus of this article is on the effect of NP diameter on the cooling efficiency of the heat sink. The heat sink has four inlets and four outlets, and it receives a constant heat flux from the bottom. CATIA and CAMSOL software were used to design the model and simulate the NF flow and heat transfer, respectively. The effects of the Reynolds number (Re) and volume percentage of nanoparticles (Fi) on the outcomes are investigated. One of the most significant results of this work was the reduction in the maximum and average temperatures of the H-S by increasing both the Re and Fi. In addition, the lowest Tmax and pumping power belong to the state of low NP diameter and higher Fi. The addition of nanoparticles reduces the heat sink maximum temperature by 3.8 and 2.5% at the Reynolds numbers of 300 and 1800, respectively. Furthermore, the highest figure of merit (FOM) was approximately 1.25, which occurred at Re=1800 and Fi = 5%. Eventually, it was revealed that the best performance of the WMH-S was observed in the case of Re=807.87, volume percentage of 0.0437%, and NP diameter of 20 nm.